1994
DOI: 10.1288/00005537-199410000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Localization of il‐1β mrna and cell adhesion molecules in the maxillary sinus mucosa of patients with chronic sinusitis

Abstract: Interleukin-1 beta (IL-1 beta) is a predominant cytokine in retained paranasal sinus fluid of chronic sinusitis where infiltration by polymorphonuclear neutrophils (PMNs) of nasal and paranasal mucosa is characteristic. The authors investigated the localization of IL-1 beta messenger RNA (mRNA) in the maxillary sinus mucosa of patients with chronic sinusitis, using digoxigenin-labeled oligonucleotide probes. IL-1 beta mRNA was detected in some extravascular PMNs and small numbers of mononuclear leukocytes but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…In general, although nonallergic patients show some evidence for neutrophilic infl ammatory process, allergic patients tend to show fewer neutrophils and somewhat more eosinophils in the infl ammatory process [ 16 , 22 ]. The relative abundance of eosinophils and fewer numbers of neutrophils in those patients with CRS and coexisting asthma suggest that this type of infl ammatory response may be independent of infection and may represent an allergic infl ammation [23][24][25][26]. However, it is also likely that infection impacts upon this disease process.…”
Section: Infl Ammatory Mechanisms In Crsmentioning
confidence: 99%
“…In general, although nonallergic patients show some evidence for neutrophilic infl ammatory process, allergic patients tend to show fewer neutrophils and somewhat more eosinophils in the infl ammatory process [ 16 , 22 ]. The relative abundance of eosinophils and fewer numbers of neutrophils in those patients with CRS and coexisting asthma suggest that this type of infl ammatory response may be independent of infection and may represent an allergic infl ammation [23][24][25][26]. However, it is also likely that infection impacts upon this disease process.…”
Section: Infl Ammatory Mechanisms In Crsmentioning
confidence: 99%
“…In the establishment of nonallergic CRS, IL-8, which is generated by neutrophils and mucosal epithelia, has been reported to play a pivotal role (6). Tokushige et al proposed that IL-1 production by neutrophils induced the expression of the intercellular adhesion molecule (ICAM-1) on endothelial cells, leading to neutrophil infiltration in CRS (7). It has been demonstrated that the peripheral blood mononuclear cells (PBMCs) of patients suffering from CRS produced large amounts of IL-13 when exposed in vitro to Alternaria species (8).…”
Section: Introductionmentioning
confidence: 99%
“…Nonallergic chronic sinusitis is characterized by purulent paranasal sinus effusion and persistent nasal discharge with numerous emigrated neutrophils [2, 3, 4, 5, 6, 7, 8, 9], in additon to the accumulation of eosinophils in the tissue [5, 10, 11, 12, 13]. Tokushiga et al [14]proposed that IL–1β induces the expression of both intercellular adhesion molecule–1 (ICAM–1) and E–selectin on ECs, presumably leading to neutrophil infiltration. The increased adhesion of neutrophils to cultured human nasal microvascular endothelial cells (HNMECs) induced by sinus effusion was significantly inhibited by anti–IL–1β antibody [3].…”
Section: Introductionmentioning
confidence: 99%